0734 Does Noise Masking Improve Sleep Consolidation In Patients Weaning From Prolonged Mechanical Ventilation?. (27th May 2020) - Shaikh, H; Chung, P; Jubran, A; Tobin, M; Laghi, F
Abstract: Introduction: Sound masking is a noise reduction strategy that adds a mixed-frequency blend of ambient sound to the environment and may improve sleep. Critically ill patients often cite noise as one of the main factors preventing sleep while they are cared for in an intensive care unit (ICU). The effect of sound masking on sleep in patients weaning from prolonged mechanical ventilation is unknown. Methods: 12-hour overnight polysomnography was obtained in eight patients undergoing weaning from prolonged mechanical ventilation. None had hearing impairment, delirium, sedation or agitation. In random order, patients were exposed to sound masking half of the recording time. Noise events were defined a 10dB increase from baseline or any sound peak over 75dB. Arousals or awakenings were attributed to noise if they occurred within 5 seconds of the noise event. Results: Environmental sound was 61.7± 0.9 dB (mean±SE) during sound masking and 55.9±1.4 dB during no sound masking. During sound masking, there were fewer sound events per hour of sleep when compared to no sound masking (4.1/hr vs 9.3/hr p=0.03). The percentage of sound events leading to a subsequent arousal or awakening with sound masking was less than during no sound masking:11% vs 22% (p=0.04). Arousal index and fragmentation index (arousal and awakenings/hr of sleep) were similar between the two conditions. In a post-study survey, five patients reported improved sleep quality with sound masking while the remaining three reported no difference. Conclusion: Sound masking decreases sound-induced arousal from sleep in patients being weaned from prolonged mechanical ventilation. Support: Veterans Administration Research Service